INTERDEPENDENCE AND FEATURES OF INTERNATIONAL BUSINESS AND CULTURAL MANAGEMENT - Rozimatov Sanjarbek Qosimjon Ugli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article considers importance of international business, importance of culture management, interdependence of directions and a number of other aspects based on the experience of modern developing countries. We are learning that the development of the twenty-first century has encouraged all countries to be advanced in almost all areas, and factors other than business and private enterprise have contributed to the comprehensive development of industries and sectors of the economy. In the course of the study we took into account the experience of the countries of the world, as well as known words, views, studies and statements of scientists not only in the economic and social spheres, but also in other spheres, and that in the future this issue will be studied more consistently. In addition, we have provided links that will help clarify the topic, conclusions, opinions and more. It should also be noted that we have paid attention to the role of culture in international business and the relevant strategy and principles of intercultural governance